Kontribusi Pajak Daerah Bagi Pendapatan Asli Daerah Guna Mendukung Pelaksanaan Otonomi Daerah di Kota Malang - Zainul Muchlas (Akutansi Bisnis & Manajemen ( ABM ), 2014)
The research activities carried out at the Regional Revenue Office in Malang, which is located on the Mayjen Sungkono Street Malang. The data of this study uses secondary data from Malang budget realization report for hotel tax and restaurant tax from 2007 to 2011. Budget Realization Report is one component of the government's financial statements presents information about the comparison of budget and actual revenues and expenditures during the year, the information can be obtained from the percentage of growth rate and the contribution of hotel tax and restaurant tax to local revenue. This research used the calculation method of the growth rate formula (Iksan, 2010) and contributions. (Halim, 2011). The results obtained by the growth rate analysis and the contribution of hotel tax and restaurant tax to Malang local revenue in accordance to the growth rate? assessment criteria (Halim, 2007) and contribute to the local tax revenue (Halim, 2011), showed that the growth rate did not succeed and very less contribute.? It can be seen from the average of growth rate of hotel tax was only 21.06%, the restaurant tax growth rate was only 22.29%, hotel tax contribution to local revenue amounted to 5.33%, and restaurant tax contribution to local revenue revenue amounted to 10.84 %. However, the realization of tax revenue for the hotel and restaurant from 2008 to 2012 were always over budgeted. So, the Malang government manages the hotel tax and restaurant tax well, but the growth rate and its contribution to local revenue still not reached the maximum yet. Therefore the government should be able to increase Malang hotel tax revenue and restaurant tax from year to year.